(untitled) (American International Journal of Supply Chain Management, 2021)
This study identified the different public utilities that are Privatised and the types of residential properties in Ibeju-Lekki in Lagos State. The area of study was stratified into high, middle, and low densities in the study area. From the records at Ibeju-Lekki government administrative office, it was further revealed that there were 56, 60, and 40 residential areas respectively on the high, medium, and low densities. Systematic random sampling selection without replacement was employed to select one of every four identified residential areas in each density, gives 14, 15, and 9 residential areas from the high, medium, and low densities respectively. There were 3,411, 1745, and 549 residential buildings in the identified residential areas. Selection of the first building in each area was done randomly while a subsequent unit of the investigation was every 20thbuilding which gave a sample size of 171, 87, and 27 residential buildings in the high, medium, and low densities respectively. One household head was selected in each building randomly. Data collected from household heads include information on the functional public utilities that are Privatised, types of buildings/ properties, the rental value of properties in the area from 2003-2015 among others. The result showed that there were six public utilities that are Privatised in the study area namely waste disposal, water supply, streetlight, road network, telecommunications, and postal service with variation in their functionality index across the densities. Finally, it was revealed that major types of residential properties identified in Ibeju-Lekki axis of Lagos State were tenement, self–contained, bungalow, the block of flats, duplex, detached and semi-detached. The household heads need to be well informed on the need for privatization of public utility to enhance the participation of household heads in the decision-making process.